The importance of preserving the freshness of fish to fulfil the tayyiban based on the analysis of scientific and Islamic jurisprudence principles - Muflih, Betania Kartika; Parson, Sitti Walida; Jamaludin, Mohd Aizat; Husman, Nur Farhanah; Elgharbawy, Amal A.M. (Rynnye Lyan Resources, 2020)
Perishability of fresh fish has become one major concern for both fish industry players as well as the consumers. If it is not properly handled and preserved, fish will be deteriorated and will lose its quality attributes. This is the point where the halalan tayyiban (lawful and wholesome) status of fish is depreciated and at the same time it affects the consumer purchase intention. This article discussed the perishability of fish, phenomenon of fish spoilage and its phases and methods which can be used to detect the deterioration. In addition, Islamic perspective on the importance of preserving the food safety, quality and halalan tayyiban status of raw fish or fish product along the processing line until reaching the consumer is also discussed according to the Maqasid al Shariah (The Objectives of Shari’ah) by using Qawaid Fiqhiyyah (Principles of Islamic Jurisprudence). The method used is the library research which includes the observation from Islamic perspectives. This is in line with achieving the highest objectives of Shariah, which is to protect the farmers, the environment, the aquaculture and the consumers. The output of the study may serve MyGAP and MS 1500:2009.